The Identity of Mapouria (Rubiaceae, Psychotrieae). Issue 5 (17th August 2020) - Taylor, Charlotte M.; Gereau, Roy E.; Callmander, Martin
Abstract: The genus Mapouria is synonymous with Psychotria, and based on Mapouria guianensis . The identity of M. guianensis, the correct name for P. mapourioides, and the identities of several other neotropical Psychotria names studied here have been unclear. The name M. guianensis corresponds to the plants currently treated as P. ernestii, and P. pedunculosa is an older name for P. mapourioides . The distinctions among the commonly confused species P. guianensis, P. carthagenensis, P. cupularis, and P. pedunculosa are clarified here, and typifications and identities are determined for several other names associated with these species.